On zeroes of the polynomials of elliptic Jacobi functions - Kholyavka, Ya.M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
An estimate of the number of zeros of the function F(r)=P(r,sn r), where P(X, Y)C [X, Y], and sn z is the Jacobian elliptic function, is obtained.